MEDIA PERMAINAN SCARBBLE GUNA MENINGKATKAN PENGUASAAN KOSAKATA - Rizki Novianti, Meiga; Wulandari, Firatih; Makhrus Ali, M. (As-Sulthan Journal of Education, 2024)
Based on the results of initial observations, classroom action research is needed which aims to improve children's vocabulary mastery through Scrabble games. The game of Scrabble is played with predetermined rules that have been modified to suit the theme. Students' vocabulary before the action was very minimal and did not develop well. Cycle I still shows a low percentage, students have a little difficulty in playing and developing understanding. It was proven that the percentage of success only reached 29%, while the percentage of failure was 71%. After taking action in cycle II, it began to show that several students were actively speaking Indonesian, this was because there were several students who already used Indonesian as their daily language. We can see that the presentation achieved 64% success. After taking action in cycle 3 using supporting media to support success, the percentage increased as expected, in cycle I 29%, cycle II 64%, cycle 3 reached 86%.